Association between splenectomy and chronic thromboembolic pulmonary hypertension: a systematic review and meta-analysis. Issue 2 (23rd February 2021) - Zhang, Liyan; Yan, Peijing; Yang, Kehu; Wu, Shanlian; Bai, Yuping; Zhu, Xinyu; Chen, Xiaojie; Li, Li; Cao, Yunshan; Zhang, Min
Abstract : Objective: Whether splenectomy increases the risk of chronic thromboembolic pulmonary hypertension (CTEPH) remains unclear. We conducted a systematic review and meta-analysis to explore the association between splenectomy and CTEPH. Design: Systematic review and meta-analysis. Data sources: PubMed, Embase and Cochrane Library databases. Methods: Two authors independently searched and extracted the data. The Newcastle-Ottawa Scale and the Strengthening the Reporting of Observational Studies in Epidemiology guidelines were used to assess the quality of the included studies, and each quality item was graded as low risk or high risk. A random-effects model was used to calculate different effective values. Results: In total, 8 trials involving 6183 participants fulfilled the inclusion criteria. The overall pooled crude prevalence of splenectomy was 4.0% (95% CI 0.03 to 0.06, I 2 =71.5%, p<0.001) in patients with CTEPH. Subgroup analysis showed a statistically significant high incidence of splenectomy in patients with CTEPH (OR=2.94, 95% CI 1.62 to 5.33, I 2 =0.0%, p<0.001) compared with patients with pulmonary arterial hypertension. There was a significantly high incidence of splenectomy in patients with CTEPH (OR=5.59, 95% CI 2.12 to 14.74, I 2 =0.0%, p<0.001) compared with patients with thromboembolism disease (venous thromboembolism or pulmonary embolism). Conclusion: The prevalence of splenectomy in patients with CTEPH was 4.0% and CTEPH might be associated with splenectomy. However, high-quality prospective trials are needed. PROSPERO registration number: CRD42020137591.